Penilaian Berbasis Test di Sekolah Minggu - Yudha Nata Saputra (Sekolah Tinggi Teologi Simpson, 2020)
Assessment as a component of learning in Sunday schools plays an important role as a measure of success in achieving Sunday school goals. Without an assessment, parents, the church, Sunday school teachers, children cannot know the extent of their success in learning in the Sunday school. This paper tries to highlight aspects of assessment in Sunday school, specifically to the factors related to the use of test-based assessment techniques that can be used in the learning process in Sunday school. It is expected that by examining the factors related to the use of test-based assessment techniques, Sunday school teachers can use them in Sunday school services that are conducted. The results of the study show that test-based assessment techniques used in Sunday schools need to pay attention to the competencies that are intended to be mastered by Sunday school children and the types of learning material delivered to Sunday school children. In addition to paying attention to aspects of competency and types of learning material, the selection of test-based assessment techniques in Sunday schools also needs to pay attention to aspects of the feasibility and economics. Penilaian sebagai salah satu komponen pembelajaran di Sekolah Minggu, memegang peranan yang penting sebagai alat ukur keberhasilan pencapaian tujuan Sekolah Minggu. Tanpa adanya penilaian maka orang tua, gereja, guru Sekolah Minggu, anak-anak tidak bisa mengetahui sejauhmana keberhasilan mereka menjalani proses pembelajaran di Sekolah Minggu. Tulisan ini mencoba menyoroti aspek penilaian di Sekolah Minggu, secara khusus kepada faktor-faktor yang terkait dengan penggunaan teknik penilaian berbasis test yang bisa digunakan dalam proses pembelajaran di Sekolah Minggu. Diharapkan dengan dikajinya faktor-faktor terkait pengunaan teknik penilaian berbasis test maka guru-guru Sekolah Minggu dapat menggunakannya dalam pelayanan Sekolah Minggu yang dilakukan. Hasil kajian menunjukkan bahwa teknik penilaian berbasis test yang digunakan di Sekolah Minggu perlu memerhatikan kompetensi yang hendak dikuasai oleh anak Sekolah Minggu dan jenis materi pembelajaran yang disampaikan kepada anak Sekolah Minggu. Di samping perhatian terhadap aspek kompetensi dan jenis materi pembelajaran, pemilihan teknik penilaian berbasis test di Sekolah Minggu juga perlu memerhatikan aspek praktibilitas dan ekonomis.